PRELIMINARY SURVEY ON ELECTRIC ENERGY EFFICIENCY IN ETHIOPIA:- AREAS OF INTERVENTION - Mamo, Mengesha (Zede Journal of Ethiopian Engineers and Architects, 2023)
In this paper the significance of electric energy efficiency improvement and major areas of loss in Ethiopia’s electric power system are highlighted for further rigorous study. Major electric energy loss areas in the utility transmission and distribution systems and consumer premises are indicated. In the consumer area the loss associated with the energy conversion devices like lamps, electric motors, electric Mittad, and welding transformers are estimated. The investigation demonstrates that there is a possibility of electric energy saving which is at least equal to 10% of the present yearly generated electric energy. Present trend in electrical engineering education; that is the inclination of students towards electronics and computer engineering areas abandoning power engineering area and the resulting danger of shortage of qualified pool of engineers for employment in the energy sector have been demonstrated. Consorted efforts of Ethiopian universities and the sector players for sustainable, efficient, reliable, and high quality electric energy supply for Ethiopia and for sustainable qualified human power training for the sector have been recommended.